Estimasi Laju Pertumbuhan Penduduk Menggunakan Metode Regresi Linier Berganda Pada BPS Simalungun - Fica Oktavia Lusiana; Indri Fatma; Agus Perdana Windarto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The Central Statistics Agency (CSA) is a non-departmental government agency that reports directly to the president. The use of data collection is for state data collection for the needs of economic strategies, infrastructure, and so on. So that the CSA institution must be able to predict the estimated rate of population growth. Particularly one of the CSA institutions in North Sumatra, CSA Simalungun, has experienced problems in estimating the population growth rate. Multiple linear regression model is the development of a simple linear regression model. If the simple linear regression model consists of only one independent variable and one dependent variable, then in multiple linear regression the number of independent variables is more than one and one dependent variable. The stages carried out in the data mining process begin with data selection from source data to target data, the preprocessing stage to improve data quality, transformation, data mining and interpretation and evaluation stages which produce output in the form of new knowledge which is expected to make a better contribution.